2000
DOI: 10.2337/diacare.23.12.1860
|View full text |Cite
|
Sign up to set email alerts
|

5-year overall survival rates of uremic type 1 and type 2 diabetic patients in comparison with age-matched nondiabetic patients with end-stage renal disease from a single dialysis center from 1991 to 1997.

Abstract: An inverse relationship between plasma insulin levels and homocysteine (Hcy) concentrations in type 2 diabetic patients has been previously reported (1) and discussed (2,3). An association between hyperinsulinemia and elevated Hcy levels has been found (4), and others (5) have observed that acute hyperinsulinemia reduces plasma Hcy levels in healthy men. In addition, it has been documented that plasma Hcy could be affected by both metabolic control and duration of disease in type 2 diabetic patients (6). By us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
1
6
0
2
Order By: Relevance
“…After the first RRT, overall survival was short in type 2 diabetic patients, with median survival times of Ͻ3.5 years, similar to reports from Europe (8,11) and the U.S. (9,12). Less than 10% of type 2 diabetic patients received RTx, as in France (20) and the U.S. (21).…”
Section: Multivariate Survival Analysis In the Whole Cohortsupporting
confidence: 57%
See 1 more Smart Citation
“…After the first RRT, overall survival was short in type 2 diabetic patients, with median survival times of Ͻ3.5 years, similar to reports from Europe (8,11) and the U.S. (9,12). Less than 10% of type 2 diabetic patients received RTx, as in France (20) and the U.S. (21).…”
Section: Multivariate Survival Analysis In the Whole Cohortsupporting
confidence: 57%
“…Available studies on patients with ESRD who have type 1 and type 2 diabetes have shortcomings because analyses were limited to patients with diabetic nephropathy (6 -7), did not differentiate the two types of diabetes (9), were short-term (10), or were based on single-center experiences (11).…”
mentioning
confidence: 99%
“…Patients with ESRD suffer from poor quality of life and shorter life expectancy compared with individuals of the same age in the general population (3,4). Those with diabetic ESRD have a much less favorable outcome than their counterparts with nondiabetic ESRD (4,7). Prevention of diabetes-related kidney disease is a key to decreasing the societal and personal burden of illness due to ESRD.…”
mentioning
confidence: 99%
“…The main findings in this study are that risk for death and annual rate of renal function decline were not significantly different according to the type of diabetes, provided that key variables such as age, sex and baseline serum creatinine are taken into account, considering two complementary statistical To the best of our knowledge, our study is the first prospective large-scale study to comprehensively examine this question, even though some previous small retrospective studies have suggested the similarity in renal outcome risk according to the type of diabetes [19,20]. The data presented here are consistent with the data from Hasslacher et al suggesting a similar risk for the development of proteinuria in type 2 and type 1 diabetes, even though these data were obtained more than 25 years ago, with different standards of care [7].…”
Section: Discussionmentioning
confidence: 90%